O seguimento da sífilis congênita em crianças tratadas ao nascer - Kawaguchi, Inês Aparecida Laudares [UNESP]; Magalhães, Daniela Mendes dos Santos [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Dias, Adriano [UNESP] (My University, 2014)
Purpose: Describe the initial clinical management and therapeutic monitoring dispensed for newborns diagnosed with congenital syphilis at birth and as of the high public hospitals in the Federal District, Brazil. Methods: Collected informations from the initial clinical management and continuity of care accorded to 81 newborns diagnosed with congenital syphilis reported to the National System of Diseases of Notification in 2008. Results: The hemogram occurred in 46.9%, and radiological long bone in 81.4%. Four children (4.9%) followed up according to the protocol of the Ministry of Health in relation to bi-monthly follow- -up until 12 months of age was 93.8% of cases ignored and found no record of complete follow-up at 18 months old of age. Conclusions: The initial clinical management and therapeutic follow-up of newborns with congenital syphilis in the Federal District is not carried out adequately and does not accordance with the guidelines set by the Ministry of Health.

Objetivo: Descrever o manejo clinico inicial e seguimento terapêutico dispensado aos recém-nascidos com diagnóstico de sífilis congênita na ocasião do parto e a partir da alta em maternidades públicas do Distrito Federal, Brasil. Método: Coletou-se informações do prontuário médico hospitalar e fichas de notificação compulsória da conduta clínica inicial e seguimento terapêutico dos 81 casos de sífilis congênita notificados ao Sistema Nacional de Agravos de Notificação, no ano de 2008. Resultado: A realização de hemograma ocorreu em 46,9%, e os exames radiológicos de ossos longos em 81,4%. Quatro crianças (4,9%) fizeram o acompanhamento conforme protocolo do Ministério da Saúde. Em relação ao seguimento bimensal até os 12 meses de vida houve 93,8% de casos ignorados e não foi encontrado nenhum registro de seguimento completo até os 18 meses de idade. Conclusão: O manejo clínico inicial e o seguimento terapêutico do recém-nascido com sífilis congênita no Distrito Federal não é realizado de forma adequada e está em desacordo com as diretrizes definidas pelo MS.
Follow-up of congenital syphilis in children treated at birth
Keywords: Syphilis; Syphilis congenital; Epidemiology; Sífilis; Sífilis congênita; Epidemiologia